Consistency of the Base-Ten System in Counting-Grid Visuals: A Content Analysis of First-Grade Elementary School Mathematics Textbooks - Lidwina Cornelia Maniboey; Tiffany Shahnaz Rusli; Rispah Purba; Alim Mutaqin (Electronic Journal of Education, Social Economics and Technology, 2026)
This study aims to analyze the consistency of the number bases used in counting-grid visual media in Grade 1 elementary school mathematics textbooks published by the Indonesian Ministry of Education, Culture, Research, and Technology, and to formulate instructional media solutions that ensure such consistency. The analysis covered two textbooks, namely Tim Gakko Kasho (2021) and Wulan (2023). The study employed content analysis using a qualitative-descriptive approach. The findings indicate that Tim Gakko Kasho (2021) uses counting-grid media with inconsistent number bases, including bases 5, 7, 9, and 10. Some pages even present two different bases simultaneously. Meanwhile, Wulan (2023) uses a 2 × 5 grid format that structurally develops base 5 before base 10. Such inconsistencies in iconic representation may lead to misconceptions about number bases, conflicts in cognitive schemas, and long-term difficulties in mastering place value and arithmetic operations in subsequent grades. Drawing on the Concrete–Representational–Abstract (CRA) framework, which aligns with Bruner’s theory of representation, and supported by the theories of Van de Walle, Ma Liping, Clements and Sarama, Piaget, and Kilpatrick et al., this article recommends the use of a 1 × 10 counting-table card with buttons as concrete or enactive media, and a 1 × 10 counting-grid image completed with writing tools as semi-concrete or iconic media. These media are proposed as solutions to ensure consistent use of the base-ten system across all stages of representation.